2 - The rise to prominence of Artemisia annual the transformation of a Chinese plant to a global pharmaceutical - Caroline Meier zu Biesen (African Sociological Review, 2010)
This paper focuses on the transformation of a recently promoted medicinal plant named Artemisia annua L. For over 2000 years, the Chinese have used A. annua as a herbal tea preparation against malaria. Pharmacological studies led to the isolation of artemisinin as the principal anti-malarial compound. Since 2001, the World health Organisation (WhO) has recommended artemisinin-based combined therapies (‘ACTs’) for the treatment of malaria – novartis is the leading actor to extract the compound in tablet form. in the 1990s, A. annua was introduced to Tanzania. Beside the local plant-based promotion of Artemisia-tea as an efficient, inexpensive natural practice to treat malaria, Tanzania hosts influential actors who seek to commercialise the plant. By following the biography of the Chinese medicinal plant, its global transfer, production, marketing, distribution, consumption, and its transformation to a highly demanded commodity, the paper critically reveals the dialectics and reciprocities between different actors and their relation to existing powerful reference systems (such as WhO, Pharmaceutical industry).